Physiological characteristics and multiple-joint isokinetic strength of upper extremity in outrigger canoe paddlers: A preliminary study - Ueda, H.; Han, I.; Kim, S.; Kiyota, H. (Isokinetics and Exercise Science, 2018)
BACKGROUND: Participation in outrigger canoe racing has gained rapidly in popularity across the United States, Australia, New Zealand, and Japan. Moreover, outrigger canoe racing has recently been included as an official sport of the 2016 Paralympic games in Rio de Janeiro. Hence, evaluation of upper limb pedaling strength in outrigger canoe paddlers would be important to determine optimal sport-specific training techniques for these athletes. OBJECTIVE: To compare multiple-joint isokinetic strength (MI) of upper extremity, muscle strength, and overall morphology in outrigger canoe paddlers and non-athletes. METHODS: Nine outrigger canoe paddlers (Out-C), and eight healthy male non-athletes (Con) were recruited. The MI of the upper extremity was evaluated using an isokinetic arm ergometer. RESULTS: Multiple-joint isokinetic strength was greater in the Out-C group than in the Con group at all pedaling speeds (p < 0.05). In addition, peak moment right arm extension and left arm (RL) was significantly greater than peak moment left arm extension and right arm (LR) only in the Out-C group (p < 0.05). Significant correlations were identified between chest girth and MI at 110 rpm, left forearm girth and MI at 50 rpm, 70 rpm, and 90 rpm, right forearm girth and MI at 50 rpm (p < 0.05). CONCLUSIONS: Asymmetries in MI of upper extremity muscles with stronger left than right side may be an important contributing feature of performance.